Assessment of humeral head perfusion after proximal humeral fracture - study protocol for evaluation of MR-based imaging techniques - Angelina Garkisch; Dagmar-C. Fischer; Thomas Mittlmeier; Sven Märdian; Bastian Klaan; Marc-André Weber; Andreas Erbersdobler; Stephan Pauly; Patrick Gahr (Journal of Orthopaedic Surgery and Research)
Abstract Background There are no clear criteria for decision-making after proximal humeral fractures, and the choice of surgical strategy and, in particular, timing is controversial. Vascular disruption can lead to delayed avascular necrosis of the humeral head, which may result in failure of the fixation procedure and the need for revision surgery. MRI pulse sequences with zero echo time (ZTE) provide “CT-like” images of the bone, while dynamic contrast-enhanced MRI (DCE MRI) allows for visualization and quantification of vascular permeability, blood flow, and clearance rates within the bone. We hypothesize that MRI with a ZTE sequence is non-inferior to CT in terms of fracture morphology specification and that DCE MRI is suitable for quantifying perfusion of the humeral head after a proximal humeral fracture. Methods This study is designed to investigate the value of modern MRI diagnostics in proximal humeral fractures. 30 patients with an acute unilateral proximal humeral fracture and an indication for ORIF with a locking plate will receive routine diagnostics (conventional X-rays and CT), supplemented by ZTE and DCE 3 Tesla MRI protocols and clinical scores. Two follow-up examinations will be performed at 3 and 6 months after surgery. Discussion As the optimal treatment method and timing of proximal humeral fractures are still controversial, the results of this study might help surgeons decide on the optimal treatment. The first aim is to evaluate the ZTE MRI sequence for its ability to assess fracture morphology compared to CT imaging. In this way, it can be decided whether or not the ZTE sequences can be considered as an alternative to CT imaging in proximal humeral fractures. The second aim of the study is to investigate the feasibility of DCE MRI for quantifying perfusion of the humeral head over a six-month period after proximal humeral fracture and ORIF with a locking plate. If the initial DCE MRI shows restricted perfusion of the humeral head, the risk of avascular necrosis may be increased, so it may be beneficial for the patient to proceed directly to reverse shoulder arthroplasty (RSA) instead of osteosynthesis with the risk of later revision. The data obtained from this study are required for the planning of a randomized trial. Trial registration DRKS-ID: DRKS00031380, MRI for acute proximal humeral fractures / - Assessment of fracture geometry with an MRI application for imaging cortical bone surfaces (Part I) / - Quantification of humeral head perfusion with Dynamic Contrast-Enhanced MRI (Part II). Acronym: Rostock MRI Study. Date of Registration 2023-06-14. Recruitment is scheduled from 1st July 2023 to 31st December 2024. The final follow-up is scheduled for June 2025. https://drks.de/search/de/trial/DRKS00031380/details;jsessionid=D961FF527EB81204EB9F211810A89B73 .